Response of Soil Moisture to Precipitation at Different Smash-Ridging Tillage Depths in Typical Sugarcane Fields in Guangxi, China - Yu Zhang; Song Wang; Lei Gan; Benhui Wei; Jinlian Zhang (Agronomy)
The purpose of this study was to identify the optimal smash-ridging tillage depth in sugarcane fields in Guangxi, China, in order to improve soil moisture conditions. Three treatments were implemented in sugarcane cultivation areas, with smash-ridging tillage depths of 20 cm, 40 cm, and 60 cm. The dynamics of soil moisture were monitored at depths of 5 cm, 20 cm, and 40 cm to investigate their response to precipitation. The results indicated that the F40 treatment had the highest mean soil moisture content. The F40 treatment exhibited a 29.85% increase in percent area of significant coherence (PASC) compared to the F20 treatment and an 8.23% increase in PASC compared to the F60 treatment. These results indicated that the F40 treatment exhibited the most significant vertical exchange. Under the same precipitation conditions, the F20 and F40 treatments exhibited a quicker soil moisture response to precipitation than the F60 treatment. The mean soil moisture replenishment (SMR) of the F40 treatment was 0.94% and 11.02% higher than that of the F20 and F60 treatments, respectively. Following the torrential rainfall event, the F40 treatment exhibited the slowest recession rate of soil moisture, indicating a greater capacity for water retention. Therefore, the smash-ridging tillage depth of 40 cm resulting in the best responsiveness to precipitation was recommended for sugarcane cultivation in Guangxi, China, which effectively improved soil moisture exchanges.